Determinants to improve the quality of E-banking services- Special focus to Eastern-Odisha region. - Sudam Sahu, Kamala Kant Das, (Dr.) Lalit Mohan Pattnayak (International Journal of Advanced Science and Technology, 2020)
The present study undertaken to assess the determinants factors that enhances the utility of e-banking service based on service quality dimensions in eastern-Odisha region. To know the extent of utility of e-banking service, the service quality dimensions are tested through the demography profile of the response based on primary study.  The study concludes e-banking is maintain efficiently the crunch of banking needs and it is responsive by customer but still there is a question mark  for reliability, accuracy. Traditional habituated banking practice and illiteracy is also questioning for convenience and tangibility. Assurance and security threat is always a obstacle for e-banking service. However, , customer services provides by e-banking service attract the customers and creates a barrier free mindset to accept the e-banking services widely with precaution and awareness of threats.